Evaluation of asthma control among children and adolescents: Cross-sectional study in West Bank, Palestine - Maher Khdour, Malek Abu Ghayyadeh, Hussam Alzeerelhouseini, Dua’a Al-Hamed, Lina Khdour (Journal of Applied Pharmaceutical Science, 2023)
This study is aiming to assess the level of asthma control and its association with clinical and demographic variables among children and adolescents with asthma. One hundred and thirty-two asthmatic children from the Primary Healthcare units of the Ministry of Health in Ramallah and Hebron participated in this cross-sectional study. An asthma control test was used to measure the patient’s asthma control. Self-practice and knowledge test was used to measure children’s parents’ knowledge about the asthma action plan, putative risk factors, peak flow meter, environmental factors, and cigarette smoking in the home. Data were entered and analyzed using SPSS 25 for windows. The result of our study indicated that 47 patients (35.6%) had controlled asthma and 85 patients (64.3%) had uncontrolled asthma. The asthma knowledge of parents was fairly good with a mean score of 6.9 ± 1.9. Univariate analysis revealed a significantly higher score of asthma knowledge for parents of controlled asthma children (7.3 vs. 6.6, t = 2; p < 0.05) than for parents of uncontrolled asthma. More parents in the controlled asthma group reported that their child tried to avoid triggers most of the time (83% vs. 64%) compared with the uncontrolled asthma control group (p < 0.05). Four variables were identified as remaining significant and associated with uncontrolled asthma: hospitalization for asthma (OR = 3.13; CI: 2.42–3.53, p < 0.05), use of systemic steroids (OR = 2.14; CI: 1.71–2.83, p < 0.05), exposure to smoke (OR = 2.31; CI: 1.65–2.77, p < 0.05), and asthma knowledge (OR = 0.39; CI: 0.09–0.77, p < 0.05). We found no significant associations with other demographic or clinical variables. More than half of the participants in this study had suboptimal asthma control during the study. More comprehensive parental/child asthma education and provision of affordable asthma care services may help improve asthma control among the children and adolescents in West Bank.